Developing a Fuzzy Inference Model for Construction Project Risk Management in Iraq - Gusson H. Al-Momen; Redvan Ghasemlounia (Journal of Techniques)
The construction industry is considered a high-risk business. Risk management is one of the most influential methods used in construction project management to increase the chances of delivering the project successfully, Risk Assessment (RA) is necessary to help organizations identify and mitigate risks; therefore, this paper suggests a framework for developing an intelligent RA. There are many Risk Factors (RF) that affect construction projects, and they vary from one country to another. In this paper, a questionnaire of forty-one questions about RF was performed; its evaluation criteria are risk probability and its impact on cost, time, and quality, this questionnaire relied on several experts’ opinions to identify the most common RF affecting Iraqi construction projects. The collected linguistic data were converted into a triangular fuzzy number. Qualitative Risk Analysis was performed to assess the priority of the identified risks; while the Adaptive Neuro-Fuzzy Inference System (ANFIS) was proposed as the intelligent model. The training outcome produced three Fuzzy Inference Systems (FISs) models evaluated using the fuzzy designer application and tested using the fuzzy designer app and MATLAB Simulink to evaluate their accuracy and reliability. Finally, a set of corrective actions were suggested to facilitate the task for users.